Pengembangan website UMKM menggunakan Blogger untuk mempromosikan suatu objek UMKM - Deya Devis Ananda; Hilda osmiati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research aims to develop a website using the Blogger platform as an effective means of promoting Micro, Small and Medium Enterprises (MSMEs) objects. Through a practical approach, this research focuses on utilizing Blogger features in increasing the visibility and marketing of MSME products. The website development methods used include responsive design, social media integration, and optimization to increase reach and appeal to consumers. It is hoped that the results of this research https://jamurmrpj01.blogspot.com/2023/12/jamur-mrjp.html can provide practical guidance for MSMEs in utilizing digital platforms to increase their marketing potential and business growth.